Urologic oncology - Merseburger, Axel S.; Burger, Maximilian (Springer, 2017)
Molecular basics on Genitourinary Malignancies.- Clinical Aspects and Investigations.-Radiological Investigations in Genitourinary Cancer -- New Imaging Modalities -- Principles of systemic therapy in urologic tumors -- The Emerging Role of immunotherapy in GU-tumors -- Bone targeted therapy -- Clinical Emergencies in Genitourinary Cancers -- Nuclear Medicine in Urological Cancer -- Strategies addressing quality of life: Patient reported outcome and symptoms management -- Pain control in genitourinary cancer patients -- Clinical trials and their principles -- GU malignancies: Prostate Cancer -- Bladder Cancer -- Renal Cancer -- Testicular Cancer -- Penile Cancer -- Other Rare Urologic Malignancies. - Diet and Genitourinary Cancer -- Systemic genitourinary Oncology